Installation of an Indole on the BRCA1 Disordered Domain Using Triazine Chemistry - Liam E. Claton; Chrissy Baker; Hayes Martin; Sergei V. Dzyuba; Khadiza Zaman; Laszlo Prokai; Mikaela D. Stewart; Eric E. Simanek (Biomolecules, 2024)
The functionalization of protein sidechains with highly water-soluble chlorotriazines (or derivatives thereof) using nucleophilic aromatic substitution reactions has been commonly employed to install various functional groups, including poly(ethylene glycol) tags or fluorogenic labels. Here, a poorly soluble dichlorotriazine with an appended indole is shown to react with a construct containing the disordered domain of BRCA1. Subsequently, this construct can undergo proteolytic cleavage to remove the SUMO-tag: the N-terminal poly(His) tag is still effective for purification. Steady-state fluorescence, circular dichroism spectroscopy, and isothermal titration calorimetry with the binding partner of BRCA1, PALB2, are used to characterize the indole-labeled BRCA1. Neither the reaction conditions nor the indole-tag appreciably alter the structure of the BRCA1. Mass spectrometry confirms that the target is modified once, although the location of modification cannot be determined by tandem mass spectrometry with collision-induced dissociation due to disadvantageous fragmentation patterns.